High Prevalence of Human Papillomavirus in Colorectal Cancer in Hispanics: A Case-Control Study - Raul D. Bernabe-Dones; Maria Gonzalez-Pons; Alejandro Villar-Prados; Mercedes Lacourt-Ventura; Heriberto Rodríguez-Arroyo; Sharon Fonseca-Williams; Francisco E. Velazquez; Yaritza Diaz-Algorri; Sofia M. Lopez-Diaz; Nayra Rodríguez; Yasuhiro Yamamura; Marcia Cruz-Correa (Gastroenterology Research and Practice)
The role of Human Papillomavirus (HPV) in colorectal carcinogenesis remains elusive. Based on the high incidence of HPV-associated malignancies among Puerto Rican Hispanics, this study aimed to assess the prevalence of HPV infection and viral integration in colorectal tissues in order to evaluate its putative role in colorectal cancer (CRC). In this case-control study, the prevalence of HPV infection in CRC (cases n = 45) and normal colon mucosa from cancer-free subjects (controls n = 36) was assessed by a nested PCR strategy. HPV-16 genotyping was performed in HPV-positive tissues and the physical status of the HPV-16 genome was determined by E2 detection. HPV was detected in 19 of 45 (42.2%) CRC cases (mean age 61.1 ± 10.7 years, 24 males) and in 1 of 36 (2.8%) controls (mean age 60.9 ± 9.6 years, 24 males) with an OR = 25.58 (95% CI 3.21 to 203.49). HPV-16 was detected in 63.2% of the HPV-positive colorectal tumors; genome integration was observed in all HPV-16 positive cases. This is the first report showing the high prevalence of HPV infections in Caribbean Hispanic colorectal tumors. Despite evidence of HPV integration into the host genome, further mechanistic analysis examining HPV oncoprotein expression and the putative role of these oncoproteins in colorectal carcinogenesis is warranted.